Public Value Creation through Mandatory Accounting Information System Success in the Public Sector: Evidence from Users of SAKTI, an Indonesian Government Finansial Application - Rizki Amalia; Ridwan; Fikry Karim; Femilia Zahra (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Purpose: This study examines how Accounting Information System (AIS) adoption and user satisfaction contribute to public value creation in the implementation of Indonesia’s Institutional Financial Application System (SAKTI), addressing the limited empirical understanding of value creation mechanisms in mandatory government information systems. Method/Approach: This research applies a quantitative design based on survey data from 99 active SAKTI users across provincial and district offices of the Ministry of Religious Affairs in Central Sulawesi. Structural equation modeling was employed to analyze the relationships among variables. Findings: The results show that system quality significantly drives AIS adoption, while information quality and organizational IS service quality primarily influence user satisfaction. Critically, AIS adoption has a significant positive effect on public value, whereas user satisfaction does not. This indicates that, in mandatory public sector systems, public value is institutionalized through consistent and integrated system adoption rather than through individual affective evaluations. Practical Implications: The practical implications of this research suggest that SAKTI needs to be managed and evaluated as an institutional mechanism for public value creation, not as a user-oriented information system. Therefore, policies within DJPb and the Ministry of Finance should prioritize system reliability, mandatory adoption, and process integration as key levers to strengthen fiscal accountability, transparency, and legitimacy of state financial management to create sustainable public value. Originality/Value: This research extends DeLone and McLean's Information Systems Success Model through the integration of Public Value Theory by asserting that system adoption is the main path of public value creation in the mandatory government financial system.